2022
DOI: 10.1159/000526872
|View full text |Cite
|
Sign up to set email alerts
|

Localized Elevation of Wall Shear Stress Is Linked to Recent Symptoms in Patients with Carotid Stenosis

Abstract: <b><i>Background:</i></b> Estimation of symptomatic and asymptomatic carotid atherosclerosis differences can be the basis for prevention and management of carotid artery stenosis disease. In clinical practice, carotid plaque vulnerability is assessed only on the basis of luminal stenosis. However, the evolution of carotid plaque from an asymptomatic state to a symptomatic one is a complex process and the underlying hemodynamic mechanisms are unknown. We aimed to investigate the differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Compared with static simulations, TA-WSS can reflect the average changes in WSS across cardiac cycles (105). Studies have shown that regions with high TA-WSS and low oscillatory shear index have larger necrotic core sizes, larger macrophage areas, and thinner fibrous caps in (167).…”
Section: Novel Hemodynamic and Biomechanical Parametersmentioning
confidence: 99%
“…Compared with static simulations, TA-WSS can reflect the average changes in WSS across cardiac cycles (105). Studies have shown that regions with high TA-WSS and low oscillatory shear index have larger necrotic core sizes, larger macrophage areas, and thinner fibrous caps in (167).…”
Section: Novel Hemodynamic and Biomechanical Parametersmentioning
confidence: 99%